Job-education match and professional mobility of selected BSHT graduates in a state university - Regatalio, Erly D.; Dare, Evangeline M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Abstract. Job-education match is an important concept in acquiring employment, promoting job satisfaction, and advancing professional mobility. It refers to the suitability or fit of one's tertiary education to the job one is currently employed in. The study investigated job-education match of selected Bachelor of Science in Home Technology (BSHT) graduates using the learned competencies derived from the syllabi-based objectives curriculum vis-a-vis the job-required competencies. It also differentiated the professional mobility of BSHT graduates whose job match with their education.
Professional Mobility Survey was used to gather data. The sample size comprised of a cohort group of 100 male and female BSHT graduates from Academic Year A.Y. 2003-2004 to 2005-2006 who followed the same version of the BSHT program. Three statistical measures were used for data analysis. The binomial test was used in obtaining the percentage match between job and education, while descriptive statistics described the graduates' professional mobility characteristics. The Kruskal Wallis Test showed the difference between the professional mobility of graduates whose job either match or do not match their education. Results of the study show that Home Management majors working as entrepreneurs used all the competencies they learned in the tertiary education. Food and Nutrition majors working in any of the three industries of food, hotel, and entrepreneurship utilized 50% of the competencies. Personality development in the subject area of home management is the most useful competency for both BSHT specializations and in all the job industries. The next useful competency is consumer education, which was utilized by Food and Nutrition majors working in the food service and entrepreneurial industries and by Home Management majors in the hotel industry. BSHT graduates in both specializations who worked in the entrepreneurial industry obtained the highest job compensation score, while Home Management majors working in the food service obtained the lowest compensation score. For job promotion, Food and Nutrition majors working in the hotel industry and Home Management majors in the entrepreneurial industry obtained the highest promotion score. For job satisfaction, BSHT graduates in both specializations are satisfied with their present jobn and relationship with co-workers, but they are only slightly satisfied with the management and their job compensation. As to professional mobility, individual workers' average professional mobility scores were subject to Kruskal Wallis Text, a tool to measure Professional Mobility of scores. Results show that there is no significant difference between graduates whose job match or do not match their tertiary education. However, with regards to the individual characteristics or components, those graduates working in the entrepreneural industry have a higher professional mobility score, especially in job compensation.
Submitted June 2018.
Thesis (Ph.D. Home Economics)--University of the Philippines Diliman
Keywords: College graduates -- Philippines -- Employment; University and colleges -- Curricula -- Philippines; Bachelor of Science in Home Technology -- Philippines -- Graduates